Konsep Mediasi Konflik Suami Istri Menurut Tafsir Surah An-Nisa’ Ayat 35 - Misbahul Munir (ASA, 2021)
Marriage is a contract or agreement made by a man and a woman who are not mahram to form a sakinah, mawaddah, warahamah household. However, it is possible that in a marriage whose purpose is to create, form, and foster a sakinah mawaddah warahmah family, disputes, squabbles, and conflicts occur between husband and wife, ranging from conflicts that seem mild, moderate, to severe such as conflicts due to economic problems, emotional problems. , love issues, third person issues and other similar issues that have the potential to lead to prolonged and protracted conflict and lead to divorce or thalaq.To overcome the occurrence of conflicts and protracted and protracted problems that lead to divorce, the Qur'an offers a very interesting concept to be used as a solution in resolving conflicts between husband and wife. The concept in question is the concept of Mediation. Mediation is a step taken by someone to resolve a dispute between two or more people by way of negotiation so as to produce a peace. Mediation is an effort to resolve conflicts by involving a neutral third party, who does not have the authority to make decisions that helps the disputing parties reach a solution (solution) that is accepted by both parties.